Impaired Aquaporin 3 Expression in Reepithelialization of Cutaneous Wound Healing in the Diabetic Rat. (July 2013) - Sugimoto, Takashi; Huang, Lijuan; Minematsu, Takeo; Yamamoto, Yuko; Asada, Mayumi; Nakagami, Gojiro; Akase, Tomoko; Nagase, Takashi; Oe, Makoto; Mori, Taketoshi; Sanada, Hiromi
Impaired cutaneous wound healing is a serious complication of diabetes mellitus (DM). Currently, little is known about reepithelialization in DM. However, recent studies identified aquaporin 3 (AQP3), a transmembrane protein that functions as a pore-like passive transporter, to be a key molecule in cutaneous epidermal wound healing. AQP3 expression is downregulated in response to tumor necrosis factor-alpha (TNF- α). Given that systemic TNF-α levels are functionally connected to impaired healing in diabetic mice and that both diabetic and Aqp3 -deficient animals exhibit impaired reepithelialization, the authors hypothesized that impaired AQP3 expression might contribute to diabetes-impaired wound healing. In the present study, the authors examined AQP3 expression in the regenerating epidermis during cutaneous full thickness wound healing and in intact skin of a streptozotocin-induced diabetic rat model. Aqp3 messenger RNA expression levels were decreased in wounds of DM rats compared to controls. Immunohistochemical analysis showed an absence of AQP3 in the stratum spinosum of the regenerating epidermis in the DM group, whereas the stratum basale was positive for AQP3 in both groups. In summary, these findings suggest that there may be a relationship between impaired AQP3 expression and diabetes-delayed reepithelialization. Thus, future nursing studies should focus on this mechanism in diabetic wound healing.